Cognitive Problems in Parkinson Disease: Perspectives and Priorities of Patients and Care Partners. Issue 1 (March 2019) - Raein, Katrina L.; Ortiz-Hernández, Samia; Benge, Jared F.
Abstract : Objective: To report how people with Parkinson disease (pwPD) and their care partners (CPs) describe the cognitive impacts of the disease, explore the convergent validity of subjective cognitive complaints (SCCs) with measures of cognition and daily functioning, and report the cognitive treatment priorities of pwPD and their CPs. Background: Cognitive symptoms in pwPD are common and disabling. Although objective cognitive impairments have been closely studied, SCCs are less well understood. Methods: Fifty dyads consisting of a person with PD and his or her CP independently completed a questionnaire that describes cognitive difficulties and was derived from a prior focus group study. Each participant rated the person with PD's degree of difficulty with symptoms and identified the top five items that would be important treatment targets. Each person with PD also completed the Montreal Cognitive Assessment (MoCA), and his or her CP completed questionnaires assessing the patient's daily functioning and the CP's distress. Results: Significant correlations existed between CP-reported cognitive symptoms and objective cognitive impairment as assessed by the MoCA. Both patient- and CP-reported SCCs were correlated with the pwPD's cognition as assessed by the MoCA, with an increasing number of SCCs reported with declining cognition. In general, the pwPD self-reported more SCCs than did the CPs, but for patients with dementia, the CPs reported more SCCs. Language and decision-making were the top treatment priorities. Conclusions: In view of the array of cognitive impacts of PD, clinicians and researchers must consider both the reporter (patient or CP) and the overall stage of a patient's cognitive decline when evaluating SCCs.